The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s10470-011-9628-3
|View full text |Cite
|
Sign up to set email alerts
|

H∞ control of multiple model subject to actuator saturation: application to quarter-car suspension system

Abstract: This paper deals with the H ? control of nonlinear systems in multiple model representation subject to actuator saturation. An application to Quarter-Car suspension system under actuator saturation is then given using the multiple model approach. The concept of so-called parallel distributed compensation (PDC) is employed for designing control system. The idea of this controller consists in designing a linear feedback control for each local linear model. To address the input saturation problem in this paper, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…In the so‐called constrained control, the control input u()k cannot be saturated. In other words, the control input is designed in such away to avoid saturation limits.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the so‐called constrained control, the control input u()k cannot be saturated. In other words, the control input is designed in such away to avoid saturation limits.…”
Section: Preliminariesmentioning
confidence: 99%
“…Motivated by the aforementioned observations, this paper intends to derive a robust H ∞ static output‐feedback control for discrete‐time fuzzy systems with cactuator saturation via FWDLF. The contributions of the proposed work are summarized as: (i)Unlike the fuzzy control design methods using a PDC controller for T‐S systems with actuator saturation, thus considering the state variables available; the presented SOF control work does not consider this strong assumption. (ii)Quadratic approaches' results , will be encapsulated into a FWDLF extended approach. (iii)The modeling errors and external perturbations are also taken into consideration via classical H ∞ attenuation using LMI constraints both for constrained and saturated control input. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] used optimal control algorithm for quarter body model. The results showed that control is better than passive suspension, but the choice of weighting coefficients mainly depends on the designer's experience, lacking theoretical basis; [4] used robust control, however not only computing increase but controller is conservative and real-time is bad; Fuzzy control does not depend on the precise mathematical model and has advantages in dealing with non-linear problems. With characteristic of self-tuning adaptive control, it can get very good control effect [5].…”
Section: Introductionmentioning
confidence: 99%